Peningkatan Minat Literasi Siswa/i Desa Limbungan dalam Menciptakan Keamanan Pendidikan - Muh. Ade Safri Salampessy; Hidayat Chusnul Chotimah (Universitas Teknologi Yogyakarta, 2024)
One of the regions of Indonesia that has issues with educational fairness is the eastern region, particularly with the distribution of educators like teachers or tutors. The East Lombok Region's Limbungan Village is one of the places where this issue is present. So, Universitas Teknologi Yogyakarta’s Community Service Team chose it’s location as the focus of community service efforts to combat that problems. In this instance, the Community Service Team and Indonesia in Village worked together to carry out community service by focusing on educational issues through the